Peningkatan Layanan Konsumen Dalam Pengambilan Keputusan pada Model Transportasi Online di Rungkut Surabaya - Acep Samsudin; Rusdi Hidayat; Hanna Tsania Nabiella; Mayra Reninta Khansa; Okalifta Rale Travito; Tarissa Seshita Hadi (El-Mujtama: Jurnal Pengabdian Masyarakat, 2023)
With the development of today's modern era, there are many conveniences that can be accessed, one of which is traveling anywhere just by using online transportation services. However, consumers have several factors to consider in choosing online transportation services. their decisions on the online transportation model in the Rungkut area, Surabaya. The variable in this study is a single variable, namely decision making in the Rungkut area community, users of online transportation services. The data collection technique used is through library research using literature such as books, previous journals and references. The results of this study are improving services to consumers so that the decision-making process carried out by the people of the Rungkut area is more confident in using the online transportation model they use. Keywords: online transportation, decision making, consumer service improvement